ANALISIS PERAN ORANG TUA TERHADAP MOTIVASI BELAJAR PESERTA DIDIK KELAS II SD NEGERI PANGGUNG KIDUL SEMARANG - Ditya Firmansyah Firman; Mei Fita Asri Untari; Ikha Listyarini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The background that drives this research is that there are some students who have low reading, writing, and numeracy skills. This has resulted in some students getting learning outcomes scores that are below the minimum completion criteria. The goal to be achieved in this study is to describe and analyze the role of parents and the obstacles experienced by parents to the student learning motivation of second grade of Public Elementary School Panggung Kidul Semarang. This research method is qualitative. Data collection techniques use observation, interviews and documentation. There are 3 stages of data analysis used, namely, data reduction, data presentation and drawing conclusions. The data of this study was obtained through subjects consisting of 10 parents students of second grade, and the teacher of second grade. Then for testing the validity of the data using triangulation. The results showed the role of parents in children's learning motivation, namely 1) Providing learning attention, 2) Guiding and accompanying children, 3) Providing advice and support, 4) providing learning facilities, 5) Providing gifts and punishments. However, some of the parents are also still lacking in providing learning attention. The obstacles experienced by parents in increasing learning motivation are 1) The condition of children who are lazy in learning, 2) The busyness of parents who cannot divide time because of work matters. It can be concluded that parents of grade II students have played a role in providing motivation for children's learning, but in providing motivation for learning there are several obstacles experienced by parents.